(untitled) - Anderson, James H. (Washington DC, 2005)
The study shows, rather disturbingly, that less progress has been made in judicial reform than in most other areas of institutional reform in these countries. The transition from socialism to capitalism requires a fundamental reorientation of legal and judicial institutions. This study reviews the environment preceding reforms, forces that provoked and supported them, and the reform agendas undertaken in these countries since 1990.
Keywords: Law and economic development,Law reform,Phát triển kinh tế và luật,Cải cách luật; Economic aspects,Khía cạnh kinh tế